Wage shocks and the technological substitution of low-wage jobs - Daniel Aaronson; Brian J. Phelan (W.E. Upjohn Institute for Employment Research, 2016)
We extend the task-based empirical framework used in the job polarization literature to analyze the susceptibility of low-wage employment to technological substitution. We find that increases in the cost of low-wage labor, via minimum wage hikes, lead to relative employment declines at cognitively routine occupations but not manually-routine or non-routine low-wage occupations. This suggests that low-wage routine cognitive tasks are susceptible to technological substitution. While the short-run employment consequence of this reshuffling on individual workers is economically small, due to concurrent employment growth in other low-wage jobs, workers previously employed in cognitively routine jobs experience relative wage losses.
Keywords: J24; J38; 330; technological substitution; routine tasks; minimum wage